Master of the mountain [compact disc, unabridged] : Thomas Jefferson and his slaves - Wiencek, Henry (HighBridge Audio, 2012)
Henry Wiencek's eloquent, persuasive book--based on new information coming from archaeological work at Monticello and on hitherto overlooked or disregarded evidence in Jefferson's papers--opens up a huge, poorly understood dimension of Jefferson's world.